2005
DOI: 10.1111/j.1399-0012.2005.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of subclinical rejection in early renal allograft biopsies for chronic allograft dysfunction

Abstract: To determine the significance of early subclinical rejection of renal allografts, we reviewed 127 biopsy specimens obtained soon after transplantation. Histological finding was categorized according to a modification of the Banff scheme as: acute rejection (AR), borderline changes (BL); non-specific inflammatory changes, (NI) and no rejection (NR). Subclinical rejection was defined as AR, BL or NI. Patients with BL or NI were divided into two groups; one was treated with high-dose methylprednisolone (MP), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 42 publications
6
34
0
Order By: Relevance
“…In other studies, patients with borderline or non-specific changes treated with methylprednisolone demonstrated reduced serum creatinine and interstitial fibrosis at 1 year compared to the untreated group (22). Corticosteroid therapy for SCR found on 1-month protocol biopsies suppressed 3-month acute Banff scores and stabilized CAN (7).…”
Section: Protocol Biopsy Of Subclinical Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, patients with borderline or non-specific changes treated with methylprednisolone demonstrated reduced serum creatinine and interstitial fibrosis at 1 year compared to the untreated group (22). Corticosteroid therapy for SCR found on 1-month protocol biopsies suppressed 3-month acute Banff scores and stabilized CAN (7).…”
Section: Protocol Biopsy Of Subclinical Rejectionmentioning
confidence: 99%
“…There is substantial variation in the reported frequency of SCR between studies, which is likely to be related to differences in patient-recipient immunological risk, ethnicity, baseline immunosuppression and era and by biopsy timing. The averaged prevalence of acute SCR (Banff 1a or above) at 1-2 weeks is 17% (range 13-25%), at 1-2 months is 29% (range 11-43%), at 2-3 months is 17% (range 3-31%) and 1 year is 18% (range 4-50%); whereas the averaged prevalence of borderline SCR at 1-2 weeks is 24% (range 12-38%), at 1-2 months is 23% (range 21-27%), at 2-3 months is 23% (range 11-41%) and 1 year is 17% (range 7-44%) from selected studies (2,5,13,14,(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Clinical Utility Of Diagnostic Protocol Biopsiesmentioning
confidence: 99%
“…as the presence of at least acute rejection grade Ia while others have also included patients with borderline changes or even nonspecific inflammatory changes (1)(2)(3)(4)11,17). The difference between borderline changes and acute rejection depends on the number of inflammatory cells in the tubular epithelium (16), but there can be some overlap between both diagnosis, since the evaluation of tubulitis is associated with a significant inter-observer variability (18,19).…”
Section: Subclinical Rejection and Graft Outcomementioning
confidence: 99%
“…1 However, as is the case for renal transplantation, unrecognized subclinical acute rejection can cause graft deterioration resulting in late graft loss. 1,25,26 A prospective study showed the importance of early diagnosis and treatment of acute rejection that prevented the deterioration of renal transplants. 27 Thus, in renal transplantation, it is important to diagnose acute rejection and treat it early.…”
Section: Discussionmentioning
confidence: 99%